The changing contributions of men and women to the level and distribution of family income: 1968 - 1988 - Maria Cancian; Sheldon Danziger; Peter Gottschalk (Levy Economics Institute of Bard College, 1991)
In the past twenty years, the labor force participation and earnings of women, especially married women, have risen dramatically. Over the same period, men's earnings have increased only modestly, and the distribution of family income has grown less equal. In this paper, we analyze the impact of changes in the level and distribution of earnings of men and women in the distribution of family income. We emphasize the contributions due to the increased work effort and real earnings of wives, as they account for a major portion of growth in family income over these two decades. Working wives have taken the place of economic growth as the factor that raises the standard of living of families across the entire income distribution. We analyze Current Population Survey data for - white, black and Hispanic families in 1968, 1978, and 1988. Our results show that the primary factor contributing to rising income inequality was the increased inequality in the distribution of husbands' earnings. Wives' earnings both raised family income and lowered inequality.
Keywords: 330